Diagnosis of urban street tree Arthur Milani street in the city Frederick Westphalen- RS - Lazzari, Laudison; Georgin, Jordana; Camponogara, Alexandre; Maggioni, Joane Helena; Oliveira, Gislayne Alves; Rosa, Ana Lúcia Denardin da (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The urban forestry provides us with a number of benefits such as welfare to the people, the best aesthetic effect, reduce the heat and air pollution, among other advantages. For these reasons it is ever more increasing the cultivation of plants in urban areas. This study aimed to survey the trees Milani Arthur Street, in order to provide scientifically grounded information to names of plants, as well as pique the interest of the local population with respect to the preservation of native and exotic examples of the regional flora. The study was conducted in the city of Frederick, a city in northwestern state of Rio Grande do Sul was evaluated and recognized across the street form the vegetation, and for all species evaluated from a form of urban trees. 25 was identified as a result of individual trees, corresponding to six different species. The most frequent species was Lagerstroenia indicates (an extremely), with a percentage of 52%, with an exotic espécie the region.